2021
DOI: 10.3389/fmed.2021.593874
|View full text |Cite
|
Sign up to set email alerts
|

Collagen Biosynthesis, Processing, and Maturation in Lung Ageing

Abstract: In addition to providing a macromolecular scaffold, the extracellular matrix (ECM) is a critical regulator of cell function by virtue of specific physical, biochemical, and mechanical properties. Collagen is the main ECM component and hence plays an essential role in the pathogenesis and progression of chronic lung disease. It is well-established that many chronic lung diseases, e.g., chronic obstructive pulmonary disease (COPD) and idiopathic pulmonary fibrosis (IPF) primarily manifest in the elderly, suggest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 318 publications
(437 reference statements)
2
38
0
Order By: Relevance
“…In addition, another FP agonist, fluprostenol, was reported to induce a decrease in the expression of COL4 and 6 that was induced by CTGF in cultured TM cells [ 52 ]. In the current study, we also found that TGF-β2 caused a significant up-regulation of the most of ECMs tested and that PGF2α or OMD induced a significant up-regulation of network-forming COL4 [ 53 ] and the down-regulation of beaded-filament-forming COL6 [ 53 ], FN, and αSMA. If 3D spheroid size and stiffness were mainly related with network-forming COL4 and fibril forming COL1, then the PG- or OMD-induced down-regulation of COL6, FN, and αSMA would result in a relative increase in COL1 content, which provides a possible explanation for why PG or OMD caused changes in both the size and stiffness of the 3D spheroids.…”
Section: Discussionsupporting
confidence: 54%
“…In addition, another FP agonist, fluprostenol, was reported to induce a decrease in the expression of COL4 and 6 that was induced by CTGF in cultured TM cells [ 52 ]. In the current study, we also found that TGF-β2 caused a significant up-regulation of the most of ECMs tested and that PGF2α or OMD induced a significant up-regulation of network-forming COL4 [ 53 ] and the down-regulation of beaded-filament-forming COL6 [ 53 ], FN, and αSMA. If 3D spheroid size and stiffness were mainly related with network-forming COL4 and fibril forming COL1, then the PG- or OMD-induced down-regulation of COL6, FN, and αSMA would result in a relative increase in COL1 content, which provides a possible explanation for why PG or OMD caused changes in both the size and stiffness of the 3D spheroids.…”
Section: Discussionsupporting
confidence: 54%
“…CFs and activated CFs are the main cell types responsible for maintaining ECM homeostasis. CFs synthesize collagen as a soluble procollagen with N- and C-terminal propeptide regions that prevent insoluble deposition [ 30 ]. Sequential processing steps are required in the extracellular space for procollagen to become a mature fibril collagen.…”
Section: Cardiac Ecm Characteristics and Homeostasismentioning
confidence: 99%
“…In healthy lung however, most ageing studies failed to identify changes to collagen presence (see reviews: [21]) and although the relative proportions of collagen I to III was shown to decrease in aged rats [71], this was not reproduced in mice [72]. In support of this, previous quantification analysis of the dataset analysed here found that the abundances of most lung collagens I and III did not change between aged and young mice [30,73]. Despite this, we identified a segment within Col1a1 displaying a significantly higher peptide yield in young than in aged (Fig.…”
Section: Collagens and Basement Membrane Proteins Among Ecm Component...mentioning
confidence: 49%
“…Interestingly, this domain is released as a functional fragment (matrikine) during the proteolytic degradation of collagen IV by membrane-anchored (MT) MMPs-14 and -15 [77,78]. Although previous analysis showed that no change in the levels of secreted MMPs [30,73], the MT-MMPs [79] were not identified. It is possible that changes in MMPs 14 and 15 exist because of ageing which may lead to differences in the levels of this fragment, reflected here.…”
Section: Collagens and Basement Membrane Proteins Among Ecm Component...mentioning
confidence: 98%